2018
DOI: 10.1038/s41540-018-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Population-based mechanistic modeling allows for quantitative predictions of drug responses across cell types

Abstract: Quantitative mismatches between human physiology and experimental models can be problematic for the development of effective therapeutics. When the effects of drugs on human adult cardiac electrophysiology are of interest, phenotypic differences with animal cells, and more recently stem cell-derived models, can present serious limitations. We addressed this issue through a combination of mechanistic mathematical modeling and statistical analyses. Physiological metrics were simulated in heterogeneous population… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 53 publications
2
80
0
Order By: Relevance
“…Translation between iPSC-CM and adult phenotypes will be critical with respect to the use of iPSC-CMs for drug safety and discovery in the human population. Gong & Sobie (2018) have developed a cross-cell type regression model that translates response to ionic current perturbations in an iPSC-CM model to the predicted the response in an adult ventricular cardiomyocyte model. Additionally, Tveito et al (2018) have developed a method of utilizing optically obtained experimental whole-cell drug-response data from immature iPSC-CMs to computationally predict the effect in a mature iPSC-CM phenotype, which serves as a more representative model of adult cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Translation between iPSC-CM and adult phenotypes will be critical with respect to the use of iPSC-CMs for drug safety and discovery in the human population. Gong & Sobie (2018) have developed a cross-cell type regression model that translates response to ionic current perturbations in an iPSC-CM model to the predicted the response in an adult ventricular cardiomyocyte model. Additionally, Tveito et al (2018) have developed a method of utilizing optically obtained experimental whole-cell drug-response data from immature iPSC-CMs to computationally predict the effect in a mature iPSC-CM phenotype, which serves as a more representative model of adult cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…While there is no analog of the HMDP for human, or other species (such as rabbit, dog, or pig) with AP features similar to human, it might be possible to extend the present study using renewable cardiomyocytes (CMs) derived from induced pluripotent stem cells (iPSC) as an alternative to the HMDP. However, iPSC-CMs and adult myocytes isolated from intact hearts exhibit quantitative differences in their responses to ionic current perturbations ( Gong and Sobie, 2018 ). Therefore, it is unclear whether the variation of ionic conductances in iPSC-CMs of genetically different subjects would be representative of the variation of conductances in intact hearts of the same subjects, which is ultimately relevant for pharmacological treatment of cardiac arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…hiPSC-CMs and adult ventricular CMs show qualitatively consistent responses to some, but not all drugs (9,20,30). Recently, two computational studies (8,31) quantitatively reported on the main electrophysiological differences between hiPSC-CM and adult ventricular CMs by comparing the Paci 2013 and O'Hara-Rudy models. Paci et al (22) investigated the discrepancies between hiPSC-CM and adult ventricular CMs by simulating the effects of pharmaceutical block of several membrane currents.…”
Section: Toward a Mature Electrophysiological Phenotypementioning
confidence: 99%